(3GdJUQjM aj TQM bUjOI cKjQ hGHf PQjMs - (3eMeO Hf GdMSf Hf eNdha GdQGTOj GdCehj GdWQGHdSj GdeZQHj, CHh YHO Gddg,J (B868 (3g` s
(3ChdgG (B:s
(3CeG HYO (B: (3CYGffG Gddg hEjGc Ydi GdYde , hhabfG Edi GdYed hGdage aEfi deG QCjJ GdYde WeSJ eYGdeg aGSJYfJ Gddg ai TQM bUjOjJjf GMOGgeG dcKjQ GHf YHO GdQMef Hf GdCShO Hf YGeQ GdNRGYi hGdCNQi dbjS Hf GdPQjM s
(3BNQgG (B:s
(3ced GdSaQ GdChd ef cJGH GdJUQjM , hKdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg hSde JSdjeG , jJdhg Ef TGA Gddg ai GdKGfi GdbUjOI GdKGfjI YaGSQa hGdMeO ddg Ydi GdJeGe s
(3GdehLhO GdSaQ GdChd hajg GdebOSGJ hTQM bUjOI cKjQs
(3JHUQI GdYfhGf (B:s
(3TQM s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B191 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs